Quartz crystal materiality in Terminal Pleistocene Lesotho. (21st January 2019) - Pargeter, Justin; Hampson, Jamie
Abstract: Abstract : The motivations of prehistoric hunter-gatherers for selecting particular lithic raw materials are often explained in rigidly functional or symbolic terms. By examining the exploitation of crystal quartz at two Terminal Pleistocene rockshelter sites (Ntloana Tšoana and Sehonghong) in Lesotho, southern Africa, the authors reveal that lithic reduction required a form of engagement unique to that material's specific properties. The preferential use of quartz crystals—irrespective of the availability of a wider range of raw materials—demonstrates agency and variability in the technological decisions.